Ewolucja od rolnika indywidualnego ku przedsiębiorcy rolnemu. Uwagi na tle statusu prawnego rolnika i spółki cywilnej - Hasińska, Izabela (Wydawnictwo Naukowe UAM, 2017)
The subject of the considerations presented in this paper are issues related to the evolution of the concept of an entrepreneur and the status of an individual farmer as an entrepreneur in comparison to the status of a partnership. Differences in the status of entrepreneurs in private and public law result in the fact that the same entities may be considered as entrepreneurs under private law but no longer as such under public law. Such a phenomenon occurs, among other things, in the event of the qualification of an individual farmer as an entrepreneur. On the other hand, a partnership has no legal subjectivity under private law. Agricultural activities carried out in the form of a partnership are performed solely by the partners themselves. However, this did not prevent a partnership from being granted the status of agricultural producer in the Act on the National Producer System, the farm register or the records of payment applications. In consequence, there arises a technical simplification that is contrary to the requirement of the clarity in the law.

L’oggetto delle presenti considerazioni riguarda l’evoluzione della nozione di imprenditore e lo status di agricoltore individuale in quanto imprenditore nel contesto dello status di società civile. Nel diritto pubblico e privato lo status di imprenditore è differente, ciò fa sì che gli stessi operatori vengano considerati imprenditori nell’ambito del diritto privato, ma non lo sono per il diritto pubblico. Il fenomeno in oggetto si verifica tra l’altro per quanto riguarda il problema di qualifica dell’agricoltore individuale come imprenditore. La società civile, invece, manca di personalità giuridica nell’ambito del diritto privato. L’attività agricola condotta in tale forma costituisce esclusivamente un’attività individuale svolta dai soci. Tuttavia ciò non è stato d’ostacolo per assegnare lo status di produttore agricolo alla società civile nell’ambito della legge sul sistema nazionale di produttori, il registro delle aziende agricole e il registro delle domande di pagamento. Si verificano così “semplificazioni tecniche”, il che non va di pari passo con il postulato di chiarezza giuridica.
Evolution from an individual farmer to an agricultural entrepreneur. Some observations with regard to the legal status of the farmer and a partnership
Da agricoltore individuale a imprenditore agricolo: un’evoluzione. Commenti nel contesto dello status giuridico di agricoltore e di società civile